All Days 2011
DOI: 10.2118/141614-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of CO2- and Methane- Foam Using Carbonate Core Material at Reservoir Conditions

Abstract: Foam has been applied to improve sweep during gas injection or for gas shut-off, and also for cleaning of contaminated underground formations. In this paper, foam properties have been evaluated for applications in carbonate material. The emphasis has been to investigate CO 2 foam, and therefore, methane and CO 2 based foam has been compared. Several foam experiments have been performed at high temperature and high pressure, respectively 100 o C and 277 bars in Limestone outcrop and carbonate reservoir cores. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 8 publications
5
46
0
Order By: Relevance
“…CH 4 -, N 2and CO 2 -foams). Strong and stable foam systems with good tolerance to oil have been found with the AOS surfactant in different porous media, at various elevated conditions and also at high pressure and high temperature field conditions (Aarra et al, 1994(Aarra et al, , 2002(Aarra et al, , 2011Solbakken et al, 2012;Vikingstad et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CH 4 -, N 2and CO 2 -foams). Strong and stable foam systems with good tolerance to oil have been found with the AOS surfactant in different porous media, at various elevated conditions and also at high pressure and high temperature field conditions (Aarra et al, 1994(Aarra et al, , 2002(Aarra et al, , 2011Solbakken et al, 2012;Vikingstad et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In Aarra et al, (2011) CO 2foam flooding in outcrop limestone cores at 277 bar and 100°C indicated possible formation of emulsion with the reservoir oil yielding very high pressure gradients. Bernard et al, (1980) also report about possible emulsions that dramatically reduced CO 2 flow through both Berea sandstone and carbonate cores.…”
Section: Introductionmentioning
confidence: 99%
“…In all foam flooding experiments conducted in this thesis (Papers 1-3), anionic alpha-olefin sulfonate (AOS) surfactant was used. The choice of foamer was based on promising results from our earlier work, screening studies and field tests using AOS surfactants (Aarra et al, 1994(Aarra et al, , 1996(Aarra et al, , 1997(Aarra et al, , 1998(Aarra et al, , 2002(Aarra et al, , 2011Skauge et al, 2002;Svorstøl et al, 1997;Vikingstad et al, 2006Vikingstad et al, , 2009. Our positive experiences with AOS surfactants for nitrogen and methane foams under elevated pressure and temperature conditions should also make comparisons against CO 2 -foams (in this thesis) interesting.…”
Section: Choice Of Surfactant In This Thesismentioning
confidence: 90%
“…The foam project builds on previous experiences and foam studies at our research institution, Uni CIPR, including field experiences with the applications of foam in North Sea reservoirs, predominately the work of Aarra et al (1994Aarra et al ( , 1996Aarra et al ( , 1997Aarra et al ( , 1998Aarra et al ( , 2002Aarra et al ( , 2011, Skauge et al (2002) and Vikingstad et al (2006Vikingstad et al ( , 2009.…”
Section: Scope and Objectivesmentioning
confidence: 99%
“…Separate measurement of foam stability was conducted for the best conditions as the results obtained from Figures 3 and 5 whereby at 1 wt% of brine, 0.5 wt% of AOS and 0.3 wt% of SNP, the most stable foams formed as shown in Figure 6. Aarra et al [45] found that the brine composition and ionic strength did not significantly affect the height of foam column. Thus, addition of 0.3 wt% of SNP has stabilized the foam system at the initial stage by coating the formation of thinning film, resulting in stronger foam by the oscillatory structural force based on mechanism proposed by [14].…”
Section: Effect Of Brine On Foam Stabilitymentioning
confidence: 97%